Environmental Risk Analysis and Control For the Development of Sustainable Urban Agriculture - Rahmayanti, Fetty Dwi; Gunawan, Andi; Fauzi, Anas Miftah; Santosa, Edi (Journal of Tropical Crop Science, 2025)
Realizing sustainable urban agriculture is one of the sustainable development goals (SDGs) targets that must be achieved. This research was conducted to analyze and explain environmental risk control for the development of sustainable urban agriculture. The research location was in East Jakarta, one of the cities in Indonesia that has implemented urban farming practices. Identification of urban agricultural environmental risks caused by biotic and abiotic factors determined of 17 categories of questions that can be represented in this research. Three risk assessment scales were used, low, medium and high risk. The environmental risk of urban agriculture caused by biotic and abiotic factors was found to have the highest risk in the air dust category. Based on the research results, it was concluded that, in general, respondents had quite effective knowledge of environmental risks but needed to increase their knowledge and deeper understanding of creating sustainable urban agriculture. Urban agriculture, due to its social, economic, and environmental benefits, should be considered part of a dynamic urban system during planning and implementation.